Pengaruh Literasi Keuangan, Perilaku Pembelian Impulsif, Dan Gaya Hidup Terhadap Penggunaan Shopee Paylater Gen Z - Restike, Karina Putri; Presasti, Dinar; Fitriani, Desfi Intan; Ciptani, Monika Kussetya (Jurnal Akuntansi Bisnis, 2024)
Several major online retailers in Indonesia have used financial services that offer online loan facilities as a form of payment. This online loan can change people’s lifestyle especially in the Gen Z generation who was born in 1995-2010. The offerings of online loan facilities may attract Gen Z that required understanding in advance technology used. Meanwhile, the majority of Gen Z still do not have an income but they have high-enthusiasm for using paylater that causes them to have high debt to cover their bills. The gen z can use paylater wisely but many of them are overwhelmed in managing pay later payments. Previous studies have investigated the effects of financial literacy, impulsive behavior, and lifestyle on the use of paylater system in Indonesia but neglected the fenomena in the gen z generation. Thus, the purpose of this research is to re-examine the influence of financial literacy, impulsive behavior, and lifestyle on the use of paylater on Gen Z in Indonesia. Using 200 respondents of Gen Z born in Indonesia, the results show that financial literacy and impulsive buying behavior have effects on the use of Shopee Pay Later in Gen Z. Meanwhile, lifestyle has no effect on the use of Shopee Pay Later in Gen Z.